The effects of cyclic tensile and stress-relaxation tests on porcine skin. (January 2018) - Remache, D.; Caliez, M.; Gratton, M.; Dos Santos, S.
Abstract: When a living tissue is subjected to cyclic stretching, the stress-strain curves show a shift down with the increase in the number of cycles until stabilization. This phenomenon is referred to in the literature as a preconditioning and is performed to obtain repeatable and predictable measurements. Preconditioning has been routinely performed in skin tissue tests; however, its effects on the mechanical properties of the material such as viscoelastic response, tangent modulus, sensitivity to strain rate, the stress relaxation rate, etc….remain unclear. In addition, various physical interpretations of this phenomenon have been proposed and there is no general agreement on its origin at the microscopic or mesoscopic scales. The purpose of this study was to investigate the effect of the cyclical stretching and the stress-relaxation tests on the mechanical properties of the porcine skin. Cyclic uniaxial tensile tests at large and constant strain were performed on different skin samples. The change in the reaction force, and skin's tangent modulus as a function of the number of cycles, as well as the strain rate effect on the mechanical behavior of skin samples after cycling were investigated. Stress-relaxation tests were also performed on skin samples. The change in the reaction force as a function of relaxation time and the strain rate effect on the mechanical behavior of skin samples after the stress-relaxation were investigated. The mechanical behavior of a skin sample under stress-relaxation test was modeled using a combination of hyperelasticity and viscoelasticity. Overall, the results showed that the mechanical behavior of the skin was strongly influenced by cycling and stress relaxation tests. Indeed, it was observed that the skin's resistance decreased by about half for two hours of cycling; the tangent modulus degraded by nearly 30% and skin samples became insensitive to the strain rates and accumulated progressively an inelastic deformation over time during cycling. Finally, the hysteresis loops became very narrow at the end of cycling and after relaxation process. Abstract : Graphical abstract: Abstract : Highlights: The effects of cyclic tensile and stress-relaxation tests on pig skin were analyzed. The skin was insensitive to the strain rate after cycling or relaxation process. A narrowing of the hysteresis loops was observed after cycling or relaxation process. The viscoelastic behavior of the skin was therefore influenced by the two tests. The skin accumulated viscoplastic strain or damage under continuous stress.